Women's Wellbeing and the Sex Ratio at Birth: Some Suggestive Evidence from India - Dhairiyarayar Jayaraj; Sreenivasan Subramanian (The Journal of Development Studies, Vol.40, No.5, June 2004, pp.91 - 119, 2004)
A declining sex ratio (SR) for a population has generally been diagnosed as an indicator of worsening female advantage, while a declining sex ratio at birth (SRB) - such as in the context of the Indian population over the recent past - has been diagnosed as being caused largely by the phenomenon of sex-selective foeticide. In this article, we examine the merits of a less sinister hypothesis in terms of which a secular improvement in women's wellbeing has led to a sex-neutral reduction in the rate of foetal wastage, and through that route, to a reduction in the SRB (and therefore in the overall SR of the population). We seek support for this hypothesis by examining evidence from India. We also discuss the implications of this line of reasoning for women's wellbeing, development and the significance of a declining sex ratio.